Calculation of electric stresses in three-core belted cables - Abdel-Salam, M. (1992)
The authors present a combined method based on inversion and charge-simulation techniques for calculating the electric field in three-core belted cables. Numerical techniques have been developed based on the charge-representation, charge-simulation and successive-imaging methods. The set of equations which describe the potential and field is solved only once with direct determination of the electric potential and field values at any time instant. This achieved higher accuracy with a very large saving in computer time in comparison with previous methods